2018
DOI: 10.1080/1120009x.2018.1487150
|View full text |Cite
|
Sign up to set email alerts
|

Poor in vivo efficacy of caspofungin, micafungin and amphotericin B against wild-type Candida krusei clinical isolates does not correlate with in vitro susceptibility results

Abstract: We determined micafungin, caspofungin and amphotericin B (AMB) minimum inhibitory concentration (MICs) and killing rates in RPMI-1640 and in RPMI-1640 with 50% serum against three Candida krusei bloodstream isolates. MIC ranges in RPMI-1640 were 0.125-0.25, 0.25 and 0.125-0.5 mg/L, in RPMI-1640 with 50% serum, MICs were 64-128-, 8- and 4-16-fold higher, respectively. In RPMI-1640 micafungin and caspofungin at 1, 4, 16 and 32 mg/L as well as AMB at 2 mg/L were fungicidal against all isolates in ≤3.96, ≤4.42 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Similar threshold values for amphotericin B have been reported for other species of Candida and filamentous fungi, such as Aspergillus. In a murine model of invasive candidiasis caused by Candida krusei, a daily dose of 1 mg/kg of amphotericin B was effective in reducing the kidney fungal burden when the MIC of the drug was of 0.125 mg/L, but ineffective when MIC was of 0.5 mg/L [42]. In another murine model study, doses of 1.5 mg/kg/day of amphotericin B resulted in a 15-day survival percentage of >50% for Candida glabrata and <25% for Candida tropicalis, the MIC being 1 mg/L for both species [43].…”
Section: Discussionmentioning
confidence: 99%
“…Similar threshold values for amphotericin B have been reported for other species of Candida and filamentous fungi, such as Aspergillus. In a murine model of invasive candidiasis caused by Candida krusei, a daily dose of 1 mg/kg of amphotericin B was effective in reducing the kidney fungal burden when the MIC of the drug was of 0.125 mg/L, but ineffective when MIC was of 0.5 mg/L [42]. In another murine model study, doses of 1.5 mg/kg/day of amphotericin B resulted in a 15-day survival percentage of >50% for Candida glabrata and <25% for Candida tropicalis, the MIC being 1 mg/L for both species [43].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, these studies are mainly related to animal models; human studies consist only of case reports and are still seldomly reported. According to the study conducted by Kardos et al [73], in vitro antifungal susceptibility and fungicidal test results did not correlate with survival of mice models of C. krusei systemic infections. In contrast, in a case of human spondylodiskitis, Pemán et al [74] found a correlation between clinical failure and MFC and time-kill curve results.…”
Section: Time-kill Curve Analysesmentioning
confidence: 94%